(untitled) - Awaji-no-Kami, Muragaki (Tokyo, Japan, 1958)
This book intrudoces about The journey from Yedo to Washington, The Japanese Embassy in the United States of America, The Embassy's Return around the Cape of Good Hope, via Java and the China Sea.
Keywords: Japan,Nhật Bản,Japan,Nhật Bản; Relations,Mối quan hệ,History,Lịch sử; America,Hoa Kỳ